2010
DOI: 10.1227/neu.0b013e3181ef2821
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Spinal Dural Arteriovenous Fistulae: A Consecutive Series of 154 Patients

Abstract: Surgical obliteration of SDAVFs is safe and very effective. Prognosis of motor function is favorable after surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
90
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(109 citation statements)
references
References 29 publications
9
90
0
6
Order By: Relevance
“…This result is in line with data from earlier studies [10,14,16,17]. Our surgical success rate of 94.7% was also comparable to previous studies [9,10]. In their meta-analysis of 16 surgical studies, Steinmetz et al [10] found that complete obliteration was achieved in 98% of patients treated with surgery and Saladino et al [9] reported complete surgical obliteration in 146 of 154 patients (94.8%).…”
Section: Treatment Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This result is in line with data from earlier studies [10,14,16,17]. Our surgical success rate of 94.7% was also comparable to previous studies [9,10]. In their meta-analysis of 16 surgical studies, Steinmetz et al [10] found that complete obliteration was achieved in 98% of patients treated with surgery and Saladino et al [9] reported complete surgical obliteration in 146 of 154 patients (94.8%).…”
Section: Treatment Resultssupporting
confidence: 91%
“…Saladino et al [9] reported complications in 5 of 154 operated patient (3.2%). In their meta-analysis, Steinmetz et al [10] found that the complication rate was lower after surgery than embolization (1.9 % vs. 3.7%).…”
Section: Treatment Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…15,26 Lowerextremity weakness is also a frequent initial symptom, usually affecting approximately half of patients, ranging from 32% to 81%. 3,8,9,15,22,24,26,30 By the time of diagnosis or surgery, symptoms have typically progressed, and almost all patients will have lower-extremity weakness. 15,18,20,22,30 Lower-extremity weakness usually involves both legs, but is asymmetrical about half of cases, 6 and even unilateral in up to 16%.…”
Section: Clinical Symptoms and Signsmentioning
confidence: 99%
“…Moreover, the standard microsurgical procedure for SDAVF involves a laminectomy or hemilaminectomy and even partial facetectomy. 14,18 In this present case, we successfully adopted a much less invasive interlaminar approach to treat lumbar SDAVF. Taking advantage of the natural interlaminar space between T-12 and L-1, the dura was opened under microscopic guidance near the middle line (where the interlaminar space was widest) to form an orifice.…”
Section: Discussionmentioning
confidence: 88%